Measurement of background radiation, cosmic ray flux and their hazard parameter of Baghdad city districts - Shafik, Shafik S. (Iraqi Journal of Physics, 2019)
The aim of this work was directed to measure the cosmic ray (CR) flux and the background (BG) absorbed dose rate for districts of Baghdad city. The maximum values of CR flux was 2.01 (particle/cm2.s) registered for several Baghdad districts and the minimum was 0.403 (particle/cm2.s) belonging to Al-kadhimiya district, whereas the overall average value was 1.24 (particle/cm2.s). The BG measurements showed that the maximum absorbed dose was 25 nSv/h belonging to Noab AL-Dhbat district and the minimum absorbed was 19.01 nSv/h observed in Al-Ghadeer district, while the overall average was 22.56 nSv/h, and this value is small than the Iraqi permissible limit, which is restricted by Iraqi Center of Radiation Protection. The hazard indices, radium equivalent activity (Raeq), absorbed dose (D), external annual effective dose (EAD), internal hazard index (Hin), and external hazard index (Hext), of TBG, were estimated and all the values of these indices are within the allowed international limits.